PENGARUH DIGITAL MARKETING DAN BRAND IMAGE TERHADAP MINAT BELI PRODUK FASHION BAJU KOKO DI MODEST CLASSY - Gunawan, Putri Rizkita; Halim, Prihartono Aksan (PROMOSI (Jurnal Pendidikan Ekonomi), 2024)
This study explores how digital marketing and brand image impact consumer interest in "baju koko," specifically in the Modest Classy market. Using quantitative methods, the research covers 384 Modest Classy consumers, with a sample size of 80 determined by the Slovin formula. Data testing in this research includes validity and reliability tests, linear regression analysis ,significance test and determinant coefficient. Based on the results of the simultaneous test, the f value is 17.50 > f table 3.12, where these results show that simultaneously the digital marketing and brand image variables have a significant effect on the purchase interest variable.. Partially, the digital marketing variable has a positive but insignificant effect with a t-value of 0.364 < t table 1.991. On the other hand, the brand image variable has a positive and significant effect with a t-value of 5.729 > t table 1.991 on the purchase interest variable.